Social media resources and export performance: the role of trust and commitment. Issue 2 (6th April 2020) - Mahmoud, Mahmoud Abdulai; Adams, Matilda; Abubakari, Aidatu; Commey, Nicholas Oblitei; Kastner, Adelaide Naa Amerley
Abstract : Purpose: The study sought to examine the influence of social media resources on export performance and the role commitment and trust play in this relationship using an integrated model. Design/methodology/approach: A quantitative survey design was employed for this study. Empirical data for this paper were drawn from 210 exporting firms in Ghana, using purposive sampling technique. The hypothesized links were analyzed using structural equation modeling. Findings: The result of this study reveals that social media resources and marketing capabilities directly influence export performance and indirectly through commitment and trust. Originality/value: To the best of the authors' knowledge, this study is among the first to attempt to use an integrated model (resource-based view and commitment-trust theory) to understand and explain an international marketing phenomenon. By concentrating on Ghana, the study offers new insights regarding the pathway for exporting firms in emerging markets.